The identification of phylloquinone in cattle samples using T.L.C. method - Bara, Lucian (Acta Agraria Debreceniensis, 2010)
A case of hemorrhage of unknown origin was observed in cattle and liver samples were submitted for assay of Vitamin K or possible cuomarol. After evaluating normal and reverse phase Thin Layer Chromatography (TLC) plates and different solvents, reverse phase TLC plate with indicator and methylene chloride:methanol 70:30 were chosen for direct method of detection and indication of Vitamin K.Gass Chromatography and Densitometry were used to quantitate the Vitamin K present in liver samples and confirmation of Vitamin K was done by Mass Spectroscopy.